Polyamine, peroxidase activity and total protein content during storage of bird-of-paradise - Vieira, Marcos Ribeiro da Silva; Lima, Giuseppina Pace Pereira [UNESP]; Vianello, Fabio; de Souza, Angela Vacaro [UNESP]; Simões, Adriano do Nascimento; de Moura, Fabiana Bezerra (My University, 2015)
The present study was aimed to the determination of the effect of storage on some biochemical characteristics (PAs content, POX activity and total protein content) of flower tissue of bird-of-paradise. Flowers were selected and labeled, avoiding any mechanical damage, and randomly distributed in recipients for two postharvest trials. In the first experiment, flowers were placed in recipients containing tap water and stored in a cold room, at 7.5°C and 90 % RH, for a period of 12 days. In experiment 2, flowers were stored in room temperature for a period of 6 days. For biochemical characteristics, samples (sepals, petals, stems and bracts) from experiment 1 were collected at 0, 4, 8 and 12 days, and at 0, 2, 4 and 6 days for experiment 2. Results showed that flower bracts, stored at 7.5°C, presented a lower content of PAs (Put and Spd), when compared to samples stored at room temperature. In both experiments, a high content of PAs (Spm) was observed in flower tissues in relation to Put and Spd. An increase of POX activity was observed in sepals stored in the cold, and was related to PAs degradation during senescence. No differences in total protein content were observed between the two treatments. The present study provides numeric results on changes in level of PAs, POX activity and total protein during postharvest of bird-of-paradise.
Keywords: Enzymes; Inflorescence; Polyamine; Postharvest; Senescence